ANALYZING ISLAMIC EDUCATION VALUES FROM BUGIS MARRIAGE PROCESS TRADITION IN BONE, SOUTH SULAWESI - Andi Mahdaniar; Hamdan Juhannis; Usman Usman (JICSA : Journal of Islamic Civilization in Southeast Asian, 2021)
This article discusses the values of Islamic education in the Bugis traditional marriage procession in the Tanete Riattang Barat sub-district, Bone district. This article uses the type of qualitative research (qualitative research). In this research, the data sources are interviews, observations, and documentation. The informants in this study were Ulama, traditional leaders and local communities. The Bugis traditional marriage procession is not a religious obligation in Islam that determines whether a marriage is valid or not, but the people in the Bugis Bone area believe that the traditional wedding procession carried out has meaning. This can be seen from every series of processions carried out based on Bugis Customs in the Tanete Riattang Barat District, Bone Regency, which can be seen from every wedding procession carried out by the people of the West Riattang Tanete District. These customs are traditions that are carried out from generation to generation and passed down from generation to generation.